Academic Bowl. (2nd September 2014) - Wax, Mark K.; Malekzadeh, Sonya
Abstract : Program Description: The academic bowl has been an annual interactive resident competition at the American Academy of Otolaryngology—Head and Neck Surgery Foundation annual meeting for the past 8 years. Four teams from across the country are selected based on strict academic criteria. These programs send 3 residents to represent them in an interactive question‐and‐answer format. The educational committees of the foundation develop questions. They are presented to the teams and the audience. Each team responds, and the audience is given a chance to pit their knowledge against the residents'. The resident team with the best score at the end of the competition wins a prize. Educational Objectives: (1) Attendees will be able to see what the current level of knowledge is in various subspecialties of otolaryngology. (2) Attendees will be able to compare their knowledge base to residents across a wide range of topics. (3) Attendees will be able to determine areas of weakness in their knowledge base as compared with residents.